Post feeding protection from Bilimbi to Motile Aeromonas Septicemia disease in African Catfish - Sefti Heza Dwinanti; Gusti Setiawan; Ade Dewi Sasanti; Madyasta Anggana Rarassari (Depik, 2021)
Bilimbi (Averrhoa bilimbi) is plant medicinal used to control fish diseases both prevention and treatment. This study aims to determine the protection period of bilimbi-fed which different duration in catfish to enhance catfish (Clariassp.) immunity in order to protect fish fromAeromonas hydrophilainfection. The Randomized Block Design Factorial (RBDF) with 2 factors was used in this experimental. The first factor (A) was the period of feeding containing bilimbi juice consisting of 3 treatments, namely 0 days (P0), 7 days (P1), and 14 days (P2). The second factor (B) was the protection period after the administration of bilimbi juice to the infection ofA. hydrophilabacteria consisting of 3 treatment, 5 days (T5), 10 days (T10), and (T15). This research was conducted at the Laboratory of Aquaculture Experiment Pond, Faculty of Agriculture, Sriwijaya University in October-December 2018. The parameters observed included prevalence of infection, growth, survival, feed efficiency and water quality. The result revealed that by giving 300 mL.kg-1 of bilimbi juice with different periods significantly affected the period of fish protection forA. hydrophilainfection.The best prevalence value was 3,33% (P2T5),and the best survival of the fish before infection was 94,17% (P2), while the best fish survival post infection was 100% (P2T5), the best feed efficiency value was 56,47% (P2), water quality under experiment were 26-29,70C for temperature, pH 6.8-7.7, dissolved oxygen 4.35-5.37 mg/L and ammonia 0.09-0.21 mg/L.Keywords:Averrhoa bilimbiAeromonas hydrophilaEthnomedicinal plantFish immunityMotile Aeromonas Septicemia